DESCRIPTIVE STATISTICS FOR DATA ANALYSIS (SOY PRODUCTION) VIA ITERATIVE PROGRAM - NETO, Alfredo BONINI; PUTTI, Fernando Ferrari; SANT’ANA, Ricardo César Gonçalves; JUNIOR, Nelson Aparecido BONINI (Revista Brasileira de Engenharia de Biossistemas, 2012)
This paper presents the development of a graphical interface, i.e., an iterative program for the study of descriptive statistical on the data of soy production in Brazil. The main goal is make a simple program and easy to understand and that can be used in various application areas, including in the area of Biosystems Engineering. These analyzes are: arithmetic mean, median, variance, standard deviation and coefficient of variation percentage. These analyzes are intended to verify if the data studied show high or low levels of dispersion. The program was developed in Matlab environment that provides all possible commands for development.